Pengembangan Karakter Siswa Melalui Pendidikan Berbasis Pondok Pesantren di MTs. Sabilul Muttaqin Pungging Kabupaten Mojokerto - Syafa'at, Wahyu (Universitas Yudharta Pasuruan, 2022)
This study aims to analyze and understand the character development of students through Islamic boarding school-based education in MTs. Sabilul Muttaqin Pungging, Mojokerto Regency, where the majority of these students are santri mukim in Islamic boarding schools so that there is collaboration between education in schools and education in Islamic boarding schools. This study uses a qualitative approach because the data presented is in the form of an explanation or narrative. Informants in this study consisted of principals, teachers, and students. The data collection technique is done by using interviews, observation, and documentation. The results of research related to education based on Islamic Boarding Schools in MTs. Sabilul Muttaqin Pungging Mojokerto Regency it can be concluded that the character development of students through education based on Islamic Boarding Schools in MTs. Sabilul Muttaqin Pungging Mojokerto Regency, it can be concluded that the character of students in MTs. Sabilul Muttaqin Pungging can be well formed as evidenced by the behavior and daily activities of those who are accustomed to maintaining discipline, courtesy, exemplary, responsibility, and istiqomah in carrying out religious activities as has been implemented in schools.